Immanuel Kant's Critique of the Ontological Argument: Challenging the Existence of God - Dina; Mohammad Muafi Himam (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This study described Immanuel Kant’s critique of the ontological argument, which he considered weak and flawed in proving the existence of God. Kant had been criticized by many philosophers -the philosophers who defended the ontological argument- as soon as he put forward the critique of the ontological argument. Immanuel Kant argued against the analyticity of